The Use of Picture Card Media to Enrich The English Vocabulary of The Eighth Graders of SMP Tri Dharma Palembang - Juliani Nur Huda; Badriyah Ulfah; Jaya Nur Iman (CV. Ulil Albab Corp, 2022)
Vocabulary is the base component of language that needs to be mastered, because it covers all of the language skills, teaching vocabulary is very important especially to students. Therefore the writer used a way to enrich vocabulary in students, namely by using picture cards media, picture card media is a type of learning media that used picture cards. The writer conducted research at SMP Tri Dharma Palembang in class VIII.B, which consisted of 45 students. The writer used a pre-experimental procedure, the data collection technique used in this research was using pre-test and post-test, before the writer gave the pre-test and post-test questions to the students, the writer conducted an instrument test for the English teacher (expert judgment), to see whether the instrument was good to use or not. After getting an assessment from expert judgment, the writer gave 25 valid questions with multiple choice a, b, c, d, and if the number of one correct value would get a score of 4, and if students answered all the questions correctly they would get 100 points. And from data analysis the writer used Paired simple t-test, it is useful to find out the whether there is a difference between the Pre-test and Post-test, and the writer used SPSS 25 program. Therefore Ho was rejected and Ha was accepted, it can be concluded that by using picture cards media can enrich vocabulary in class VIII.B SMP Tri Dharma Palembang.